The Persistence of Victim Blaming in Child Rape Trials: A Victimological Analysis of the Banjarmasin High Court Acquittal - Liantha Adam Nasution; Zul Fahmi; Sumardi Efendi; Ahmad Rozali; Maulana Muklis; Muhammad Asim Rafiq (NUSANTARA: Journal Of Law Studies, 2026)
This study examines the extent to which victim blaming shapes judicial reasoning in child rape trials, focusing on the acquittal in Decision No. 42/PID/2017/PT Bjm and addressing a gap in systematic appellate-level analyses of PERMA No. 3 Tahun 2017 implementation. It employs doctrinal legal analysis combined with qualitative content analysis of two primary decisions—Decision No. 20/Pid.B/2017/PN Mrh and the aforementioned appellate ruling—and evaluates them against relevant normative frameworks, including the Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), and Undang-Undang Tindak Pidana Kekerasan Seksual. The findings indicate that the appellate panel systematically shifted the evidentiary burden onto the child victim by privileging her conduct while discounting non-physical forms of coercion and psychiatric evidence of trauma. This pattern operationalises notions of victim precipitation and conflicts with procedural and protective norms, thereby producing secondary victimisation through courtroom rhetoric that denigrates victims. Conceptually, the article advances an integrated analytical framework that combines the ideal-victim construct, victim blaming, and secondary victimisation to interpret appellate reasoning, thereby refining the role of victimology as a trauma-informed evaluative lens for judicial texts. Juridically, the findings reveal a structural tension between appellate practice and KUHAP’s recognition of psychological harm as valid evidence, as well as PERMA No. 3 of 2017’s prohibition of victim-blaming conduct, with broader implications for child protection, judicial integrity, and public confidence in the justice system. The study therefore recommends targeted reforms: explicit statutory recognition of non-physical coercion and psychiatric evidence; enforceable ethical sanctions and monitoring mechanisms to ensure PERMA compliance; trauma-informed judicial training; and harmonised institutional measures that internalise child-protection principles, including the integration of Islamic law–informed recommendations within a broader institutional harmonisation framework to ensure alignment with national pro-victim legal reform.